Acid/base-controlled chemodivergent synthesis of two differently functionalized tetrahydroimidazo[1, 2-a]pyridines1. Issue 86 (18th September 2015) - Guo, Wei-Si; Xin, Xing; Zhao, Ke-Long; Wen, Li-Rong; Li, Ming
<x xml:space="preserve">Abstract</x> Two differently substituted type of imidazo[1, 2-a]pyridine derivatives were synthesized chemodivergently using β-ketothioamides, aldehydes and heterocyclic ketene aminals through acid/base regulation.